Penerapan Teknik Coaching Dalam Meningkatkan Kompetensi Kepala Madrasah pada Supervisi Pendidikan - Radhiyah; Susi Yusrianti (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
Educatinal Supervision is an activity in controlling, directing, guidancing, evaluating and improving the performance of the teachers and staff in teaching leraning proses. Coaching technique is a form of supervition than can be applied in Educational Supervision. This study aims to analtze the application of coacging technique in improving the headmaster’s competency in educational supervision. This study uses the systematic literature Review (SLR) approach. The cata collection technique uses a Google Scholar through the Publish or Parish software. The keywords used are “coaching in Educational Supervison “the year starting from 2018 to 2022 restrictions. Researcer used 7 articles that were directly related to caching cundacted by the headmaster of Madrasa in improving academic supervision competency. The result of the study show that the coaching technique used can improve the supervisory competency of headmaster of Madrasa in maximizing the performance and teacher’s ability in solving the problems.